PENGARUH KEPEMIMPINAN DAN ETIKA KERJA TERHADAP MOTIVASI KERJA PADA USAHA KERUPUK SAMBAL SPESIAL SIBOLGA - Tongonizisokhi Laia; Nelly A.Sinaga; Kaharuddin (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
The Influence of Leadership and Work Ethics on Work Motivation in the Sibolga special chili cracker business. This study aims to determine how much influence Leadership and Work Ethics have on Work Motivation in the Sibolga special chili cracker business, the model used in this study is a quantitative descriptive method and the data collection technique uses a questionnaire, using 30 samples. And the method of analysis used is multiple linear regression analysis, and t test and f test, to find out the independent variables that affect the dependent variable, in managing this data using the SPSS for Windows version 20 tool. The results of this study indicate that leadership has a positive effect and Work motivation has a negative effect, but simultaneously all variables have a significant positive effect with a value of 0.002 on work motivation in the Sibolga special chili cracker business, which also means that the hypothesis proposed is accepted, while the results of the partial analysis of leadership have a significant influence on work ethics negative and insignificant effect on work motivation in the Sibolga special chili cracker business.